RAGAM KEPRIBADIAN MANUSIA DALAM TAFSIR BUYA HAMKA - Sari, Linda Mayang; Ananda, Yassinta; Markos, Toni; Ulfitri, Annisa; Summalia, Rika (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
In the Al-Quran this discussion of personality is also explained. However, it does not use standard terms as in psychology. One of the commentators who interpreted these verses was Buya Hamka in the Al-Azhar commentary. Buya Hamka, from his diverse essays and more of his works which have a tasawuf style, reviews verses about personality from the perspective of Hamka's interpretation, so it is very relevant considering that personality is synonymous with tasawuf. This research belongs to qualitative research with a library research approach. The data source uses the Al-Azhar interpretation book as the main reference in understanding the verses being interpreted. And secondary sources in the form of articles, journals, theses, and other scientific works. The results of his research are Buya Hamka's interpretation of positive and negative personalities in the Qur'an. A positive personality emerges and is formed by two main things, the first is to purify the soul and the second is to calm the soul. Because a positive personality will emerge from these two things. Buya Hamka's interpretation of negative personality in the Qur'an. Negative personalities arise and are formed by the main factor, namely humans who always follow their passions. Those who follow these passions will later become regretful people.